Optic Pathway Glioma in Children with Neurofibromatosis Type 1: A Multidisciplinary Entity, Posing Dilemmas in Diagnosis and Management Multidisciplinary Management of Optic Pathway Glioma in Children with Neurofibromatosis Type 1 - Lohkamp, Laura-Nanna; Parkin, Patricia; Puran, Allan; Bartels, Ute Katharina; Bouffet, Eric; Tabori, Uri; Rutka, James Thomas (Frontiers in Surgery, 2022)
Introduction: Neurofibromatosis type 1 (NF1) has an incidence of 1 in 2000 to 3000 individuals and in 15% is associated with optic pathway glioma (OPG). Given the variability in clinical presentation and related morbidity, a multidisciplinary approach for diagnosis and management of children with NF1 and OPG is required, but often lacks coordination and regular information exchange. Herein we summarize our experience and describe the care pathways/network provided by a multidisciplinary team. The role of the distinct team members is elucidated as well as the care amendments made over time. Methods: We performed a retrospective single-center observational study, including children treated at our institution between 1990 and 2021. Inclusion criteria were clinical diagnosis of NF1, radiographic and/or histopathological diagnosis of OPG and age below 18 years. Patients being treated elsewhere were excluded. Data was abstracted from each child’s health record using a standardized data collection form. Characteristics of children with NF1 and OPG were described using means (SD) and percentages. Outcomes were determined using Kaplan-Meier estimates. Results: From 1990 to 2021, 1337 children were followed in our institution. Of those, 195 were diagnosed with OPG (14,6%), including 94 (48.21%) females and 101 (51.79%) males. Comprehensive data were available in 150 patients. The mean (SD) age at diagnosis was 5.31(4.08) years (range: 0.8 - 17.04 years). Sixty-two (41.3%) patients remained stable and did not undergo treatment, whereas 88 (58.7%) patients required at least one treatment. The mean (SD) duration of follow up was 8.14 (5.46) years (range: 0.1-25.9 years; median 6.8 years). Overall survival was of 23.6 years (1.08), comprising 5 deaths. A dedicated NF clinic, including pediatricians and a nurse, provides regular follow up and plays a central role in the management of children with NF1, identifying those at risk of OPG, coordinating referrals to Neuroradiology and other specialists as indicated. All children are assessed annually by Ophthalmology. Comprehensive care was provided by a multidisciplinary team consisting of Dermatology, Genetics, Neuro-oncology, Neuroradiology, Neurosurgery, Ophthalmology and Pediatrics. Conclusions: The care of children with NF1 and OPG is optimized with a multidisciplinary team approach, coordinated by a central specialty clinic.